On the Double of the Emad - Falih Transformation and Its Properties with Applications - M. Turq, Saed; A. Kuffi , Emad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In this paper, we have generalized the concept of one dimensional Emad - Falih integral transform into two dimensional, namely, a double Emad - Falih integral transform. Further, some main properties and theorems related to the double Emad - Falih transform are established. To show the proposed transform's efficiency, high accuracy, and applicability, we have implemented the new integral transform for solving partial differential equations. Many researchers have used double integral transformations in solving partial differential equations and their applications. One of the most important uses of double integral transformations is how to solve partial differential equations and turning them into simple algebraic ones. The most important partial differential equations are Laplace, Poisson, wave, heat, telegraph, and other equations. A new Double Emad -Falih integral transform denoted by the operator , the transform form is as follows: